Educating users to generate secure graphical password secrets: An initial study - Fatehah M.D.; Jali M.Z.; Wafa M.K.; Anuar N.B. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus